EFFECTIVENESS OF PROBIOTIC SUPPLEMENT ON HELICOBACTER PYLORI INFECTION ERADICATION IN GASTRIC ULCERS - Sulistyanti Dian Rachmawati; Wiji Lestari (Perhimpunan Dokter Gizi Klinik Indonesia, 2023)
Background: Helicobacter pylori colonizes the gastric mucosa in 50% of the human population. H. pylori infection causes several upper gastrointestinal tract diseases such as chronic gastritis, peptic ulcer, duodenal ulcer, and gastric cancer. H. pylori is also associated with a high risk of developing gastric adenocarcinoma. The World Health Organization classifies H. pylori infection as a class 1 carcinogen. Giving probiotics may improve the immune system and suppress the effects of pathogens. However, mixed results were obtained from the use of various kinds of bacteria and fungi as probiotics. Objective: To determine the effectiveness of probiotic supplementation against the eradication of Helicobacter pylori infection in gastric ulcers. Conclusion: The effectiveness uses of probiotics to eradicate H. pylori has not been proven. It will take clinical trials with a sufficient number of subjects and certain probiotic strains to be able to determine the type of strain, dosage, duration of use, and side effects that can be caused.